Facile synthesis of carbon-doped mesoporous anatase TiO2 for the enhanced visible-light driven photocatalysis - Liu, J.; Zhang, Q.; Yang, J.; Ma, H.; Tade, Moses; Wang, Shaobin; Liu, Jian (The Royal Society of Chemistry, 2014)
Here we report a low-cost and facile synthesis approach for carbon-doped mesoporous anatase TiO2 by using Ti(BuO)4 as a source for both Ti and carbon through xerogel carbonization in a hypoxic atmosphere. The resultant mesoporous C-TiO2 with high crystallinity exhibits excellent photocatalytic activities for degradation of methyl orange (MO) and phenol under visible light irradiation.